Legal Aspects of the Duplication of Economic Public Utilities Subject to Public Law and Private Law - Study in Algerian Legislation – - Boudjelti, Azz El-Din (Journal of Legal Studies and Researches, 2022)
If administrative public facilities are considered as the only category present on the front, then economic facilities, despite their actual presence as activities. However, their importance increases with the increasing legislative and regulatory texts. This is on the one hand. From an other hand, we find that these legal provisions regulating the public economic facility combine the general rules familiar in administrative law, and the special rules familiar with civil law, commercial law, etc